Estimating the COVID-19 Prevalence in Spain With Indirect Reporting via Open Surveys - Garcia-Agundez, Augusto; Ojo, Oluwasegun; Hernández-Roig, Harold A.; Baquero, Carlos; Frey, Davide; Georgiou, Chryssis; Goessens, Mathieu; Lillo, Rosa E.; Menezes, Raquel; Nicolaou, Nicolas; Ortega, Antonio; Stavrakis, Efstathios; et al. (Frontiers in Public Health, 2021)
During the initial phases of the COVID-19 pandemic, accurate tracking has proven unfeasible. Initial estimation methods pointed towards case numbers that were much higher than officially reported. In the CoronaSurveys project, we have been addressing this issue using open online surveys with indirect reporting. We compare our estimates with the results of a serology study for Spain, obtaining high correlations (R squared 0.89). In our view, these results strongly support the idea of using open surveys with indirect reporting as a method to broadly sense the progress of a pandemic.